EL CONSUMO DE DROGAS EN LA MUJER COSTARRICENSE - Bejarano, Julio (1994)
The epidemiological research conducted by the Instituto sobr eAlcoholismo y Farmacodependencia in 1990, serued to anallze the prevanlence of the use and abuse of alcohol, tobacco, coffee, psychoterapeutlc and illicit drugs, ln costarrican women aged 12 to 70. This article analizes demographic data and its relationship with the moderate use and abuse, more than drug addiction and describes some relevant fields to formulate politics and general intervention.